Uso de instrumentos de avaliação de riscos ergonômicos: teoria e prática - Souza, Viviani Cintra de (2011)
In recent years, in Brazil, companies have shown a growing interest in developing actions to address ergonomic problems in working conditions related to health and productivity. This interest is due in part to the compliance requirements of working conditions to the legislation of the Ministry of Labor and Employment. To adapt working conditions to the legal conditions recommended the need arises to measure the conditioning factors of work activities, and consequently increases the demand for use of instruments to assess the ergonomic risks. The study aims to determine the contribution of risk assessment tools in the analysis of ergonomic conditions of work activity in steps of Ergonomic Work Analysis and use of these instruments in Brazil, by consulting firms and research institutions and extension in the area ergonomics in an attempt to establish the relationship between the objectives and content of the instruments and methods of analysis used in practice. The survey was conducted through a literature review, to determine the instruments and through a questionnaire, seeking, knowing the tools most used by Brazilian organizations to ergonomics. In the questionnaire some questions were addressed in order to know the work of organizations of ergonomics in Brazil: issues relating to training for professionals working with ergonomics, the main intervention activities and steps that develop, the factors related to the job consider during the intervention, the methodologies we use as reference and the instruments they use to ergonomic risk assessments. According to the systematic knowledge and accumulated in the literature on the use of tools to verify specific aspects of man's relationship with their work environment, it was observed that most concentrate their goals in the evaluation of factors related to the physical dimensions of the work. The research results allow us to conclude that the instruments are not sufficient to analyze the work during an ergonomic intervention. Thus, the formation of analysts with their different views and